Field testing of fungicides for the control of leaf scald disease of rice - DAS, S.R. (Indian Phytopathology, 2002)
Leaf scald of rice caused by Gerlachia oryzae (Hashioka and Yokogi) Gams once considered to be a minor disease, has now become a potential threat to rice production during wet season in most of the eastern and north-eastern states of India and Bangladesh. Considering lack of resistance in the presently cultivated commercial varieties and the yield loss upto 30% in unprotected crop, a field trial was laid out for two consecutive years to evaluate the relative efficacy of certain fungicides in reducing the leaf scald disease.